The Role of Decision-Making Biases in Ireland's Banking Crisis - LUNN, PETE (ESRI, 2011)
This paper considers Ireland's banking crisis from the perspective of behavioural economics. It assesses whether known biases in judgement and decision-making were instrumental in the development and severity of the crisis. It investigates evidence that key decision-makers, including consumers, businesspeople, bankers and regulators, as well as parties such as civil servants, politicians, academics and journalists, were influenced by seven specific phenomena which have been identified previously via experiments and field studies. It concludes that evidence is consistent with the influence of these established phenomena. Ireland's long boom, rapid financial integration and lack of relevant past experience may have increased the vulnerability of decision-makers to economic and financial reasoning that proved disadvantageous. The analysis has potential implications for attempts to prevent future crises.
PUBLISHED
Keywords: Behavioural economics; Ireland; Decision-making biases; Financial crises; Economics